1995
DOI: 10.1002/mrm.1910340611
|View full text |Cite
|
Sign up to set email alerts
|

Locally focused mri

Abstract: Conventional magnetic resonance images are reconstructed by Fourier transformation and have uniform spatial resolution across the entire field of view (FOV). This paper describes a way of creating MR images that have higher spatial resolution in some areas than in others. High resolution imaging can be confined to just those areas where it is necessary to resolve strong edges without truncation artifact. Such locally focused images can be acquired in less scan time than that required to image the entire FOV wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…For example, the usual sampling theorem can be applied to find the k-space measurements required to reconstruct each zone (HR, LR) separately. As reported elsewhere [20], the LF MRI method worked quite well when it was applied to the collection of all of these k-space points, taken together.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the usual sampling theorem can be applied to find the k-space measurements required to reconstruct each zone (HR, LR) separately. As reported elsewhere [20], the LF MRI method worked quite well when it was applied to the collection of all of these k-space points, taken together.…”
Section: Discussionmentioning
confidence: 98%
“…However, previous experiments [21] suggested that the SBS solutions produce L F reconstructions with reasonably small error.…”
Section: Calculation Of New Basis Functionsmentioning
confidence: 96%
“…"Dynamic" features (i.e., the small structures in the "dynamic" image but not in the baseline image) are not depicted clearly in these projections, showing the inadequacy of these basis functions for dynamic imaging. The right panels of the second and third rows show the projections of the same "dynamic" image onto the first 12 and 16 basis functions, respectively, derived from the SVD of the baseline image in the upper right panel. Fewer artifacts are present, indicating that the second basis function expansion converges more rapidly to the "dynamic" features.…”
Section: Discussionmentioning
confidence: 99%
“…The upper left panel shows a simulated 64 x 64 "dynamic" image with a central void ("ventricle"), one large "lesion," and numerous small "dynamic" features. The left panels of the second and third rows are the projections of this image onto the first 12 and 16 basis functions, respectively, which were derived from the SVD (or principal components analysis) of a nearly structureless baseline image (upper middle panel). "Dynamic" features (i.e., the small structures in the "dynamic" image but not in the baseline image) are not depicted clearly in these projections, showing the inadequacy of these basis functions for dynamic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these methods in fact shift sampling requirements to excitation, requiring RF pulses that are longer than desired. Methods that employ non-Fourier analyses via phase encoding [7,8] necessarily introduce data extrapolation errors.…”
Section: Introductionmentioning
confidence: 99%